Assessing energy benefits of operating anaerobic digesters at low temperature with solids pre-ozonation. (January 2018) - Bakhshi, Zeinab; Jauffur, Shameem; Frigon, Dominic
Abstract: Anaerobic digestion of sludge is one of the most widely used processes for biogas and energy production. Conventionally, anaerobic digesters are operated at 35 °C to overcome the hydrolysis rate-limiting step. However, the energy expenditure for heating anaerobic digesters may be significant. The feasibility of operating anaerobic digesters at low mesophilic temperature (20 °C) by combining sludge ozonation was studied. Operation of three anaerobic reactors for 350 days showed that integrating solids ozonation and anaerobic digestion at 20 °C led to a higher volatile suspended solids (VSS) destruction of 60% than anaerobic digestion at 35 °C with raw sludge. Methane production in the reactor at 20 °C with sludge ozonation was enhanced from 62.6 mL CH4 /g VSSin to 71.3 mL CH4 /g VSSin for the 35 °C digester without sludge ozonation. Energy analysis showed that the 20 °C-ozonated digester produced 35% more energy than the 35 °C digester, with a net energy balance of +174 GJ/d and +129 GJ/d, respectively. The 20 °C-ozonated digester had a higher Energy Sustainability Index (ESI) (2.88) than the 35 °C digester (2.33) suggesting a more energetically sustainable option. Highlights: Anaerobic digestion was operated at low mesophilic temperature (20 °C). To overcome the slow rate-limiting step of hydrolysis, sludge ozonation was performed. Higher volatile suspended solids (VSS) destruction of 60% was obtained at 20 °C with ozonation than at 35 °C with raw sludge. Energy efficiency of conventional anaerobic digester and at 20 °C combining sludge ozonation was evaluated. 35% more energy was produced at 20 °C with ozonation than at 35 °C with raw sludge.